Implementation of Restorative Justice in the New Criminal Code: A Normative Analysis of Criminal Case Resolution - Henny Saida Flora; Taqyuddin Kadir; Ichsan Sjuhudi (PT. Anagata Sembagi Education, 2026)
This study examines the application of the restorative justice approach in the New Criminal Code (KUHP) enacted through Law Number 1 of 2023. The background of this study is the increasing need for a more humane and effective criminal case resolution system that simultaneously takes into account the interests of victims, perpetrators, and the community. The New Criminal Code brings a significant paradigmatic shift by integrating the principles of restorative justice into Indonesian positive legal norms. The research method used is normative legal research with a statute approach, a conceptual approach, and a comparative approach. The results show that the New Criminal Code explicitly accommodates the principle of restorative justice through several provisions, including: the regulation of recovery-oriented sentencing objectives (Article 54), a settlement mechanism outside the judicial process (Article 70), and provisions on supervisory punishment and rehabilitative measures. However, its implementation faces a number of normative challenges, including the lack of comprehensive technical regulations, limited institutional capacity, and the need for harmonization with other laws and regulations. This study recommends the development of detailed implementing regulations, strengthening the capacity of law enforcement officials, and developing an institutional infrastructure that supports the optimal implementation of restorative justice in the Indonesian criminal justice system.